Mokslo ir mokymo dalyko santykis teikiant aukštąjį bibliotekinį ir bibliografinį išsilavinimą. (Problemos formulavimas) (rusų k.) - Gudauskas, Renaldas (Knygotyra, 1988)
The subject-matter of education is one of the main elements of the didactic system. The correct determination of the main subject-matter of education enables the achievement of educational goals. Education and higher education are closely interconnected. However, one of the main problems in professional pedagogy—the relationship between science and the subject-matter of education—has not yet been fully resolved. This problem is particularly urgent in the training of skilled librarians and bibliographers because library and bibliography sciences are relatively young and rapidly developing. The author asserts that it is necessary to create a special theory of higher education in librarianship and bibliography, which would allow for the improvement of this field according to the latest tendencies in the development of library and bibliography sciences, informatics, and the science of the book. It is essential to analyze the logical structure of these sciences, to identify their main components and methods that influence the construction of corresponding branches of education. The author proposes a preliminary solution to this problem.